2018
DOI: 10.1007/s40290-018-0243-9
|View full text |Cite
|
Sign up to set email alerts
|

Excipients in Neonatal Medicinal Products: Never Prescribed, Commonly Administered

Abstract: To attain effective and safe pharmacotherapy, formulations in (pre)term neonates should enable extensive dose flexibility. During product development and subsequent authorization and clinical use of such formulations, there is also a need for informed decisions on excipient exposure: in addition to the need to improve the knowledge on active compounds, there is a similar need to improve the knowledge on excipients in neonates. Excipients are added to formulations as co-solvent, surfactant, preservative, colora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 37 publications
(59 reference statements)
0
36
0
Order By: Relevance
“…A risk of exposure to excipients through the oral administration route exists, since excipients are used in oral dosage forms to improve, for instance, patient acceptability, the solubility of the drug substance or the shelf-life of the drug product [10]. Excipients such as preservatives, colorants, sweeteners, ethanol and propylene glycol can be harmful to children, especially for infants and neonates [10][11][12]. Garcia-Palop et al discovered in a Spanish University Hospital that at least one harmful excipient was present in 62% of orally administered drugs used for neonates [13].…”
Section: Introductionmentioning
confidence: 99%
“…A risk of exposure to excipients through the oral administration route exists, since excipients are used in oral dosage forms to improve, for instance, patient acceptability, the solubility of the drug substance or the shelf-life of the drug product [10]. Excipients such as preservatives, colorants, sweeteners, ethanol and propylene glycol can be harmful to children, especially for infants and neonates [10][11][12]. Garcia-Palop et al discovered in a Spanish University Hospital that at least one harmful excipient was present in 62% of orally administered drugs used for neonates [13].…”
Section: Introductionmentioning
confidence: 99%
“…The participants in this study believed that, in case the printing method used does not enable printing of a QR code, other measures should be taken to ensure identification of the drug product and, thus, to prevent medication errors. In drug development of pediatric medicines, one must consider that the colorant as well as other excipients are safe for use in children, since investigations have shown that neonates and infants are extensively exposed to harmful excipients during oral administration of medicines [38][39][40]. Furthermore, this study shows that healthcare professionals prefer dosage forms containing excipients that enable the administration of the dosage form through enteral feeding tubes as well as after dissolving or dispersing the dosage form in liquid, e.g., water.…”
Section: Main Findingsmentioning
confidence: 99%
“…This rapid growth of cell receptors leads pediatric patients to give toxic and fast responses to different excipients. 17,18 Pharmaceutical excipients are necessary to maintain the quality and improve patient acceptability of medicines. Excipients ideally have limited pharmacological activity; however, some are associated with toxicity in neonates.…”
Section: Dovepressmentioning
confidence: 99%
“…43 As the WHO and FDA recommended, the maximum amount of ethanol in pediatric medications should not be more than 0.5% v/v for children under 6 years, 5% for children 6-12 years, 10% for children over 12 years. 17 The American Academy of Pediatrics (AAP) also established that the quantity of ethanol in pediatric formulations should not produce a blood concentration higher than 25 mg/100 mL after the administration of a single suggested therapeutic dose. 44 Propylene Glycol and Polyethylene Glycol Propylene glycol (PEG) is a dihydroxy alcohol used as a pharmaceutical solvent, preservative, and humectant.…”
Section: Ethanolmentioning
confidence: 99%
See 1 more Smart Citation